2006
DOI: 10.1128/jvi.00542-06
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Human Immunodeficiency Virus Type 1 in Untreated Infection Occurs Preferentially within Genes

Abstract: Previous analyses of human immunodeficiency virus type 1 (HIV-1) integration sites generated in infections in vitro or in patients in whom viral replication was repressed by antiviral therapy have demonstrated a preference for integration within protein-coding genes. We analyzed integration sites in peripheral blood mononuclear cells (PBMCs), spleen, lymph node, and cerebral cortex from patients with untreated HIV-1 infections. The great majority of integration sites in each tissue were within genes. Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 22 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…These loci, in which vector insertion is highly enriched, are of interest not only to the gene-trap community, but also to the gene therapy [19], cancer biology [20], and HIV fields [21]. Prior attempts to define hotspots have likely been confounded by ignoring effects of expression and length that we define here.…”
Section: Resultsmentioning
confidence: 99%
“…These loci, in which vector insertion is highly enriched, are of interest not only to the gene-trap community, but also to the gene therapy [19], cancer biology [20], and HIV fields [21]. Prior attempts to define hotspots have likely been confounded by ignoring effects of expression and length that we define here.…”
Section: Resultsmentioning
confidence: 99%
“…However, the first analysis of HIV-1 integration sites in infected individuals found that HIV-1 proviruses integrated into transcriptionally active cellular genes in resting CD4 ϩ T cells from patients on HAART (18). The same pattern has been observed in peripheral blood mononuclear cells (PBMC) from untreated individuals (36). In these studies, integrated proviruses were detected by specific PCR strategies, but the replication competence of the proviruses was not assessed.…”
mentioning
confidence: 86%
“…Studies have now shown that both gamma-retroviruses and lentiviruses preferentially integrate in transcriptionally active genes [24][25][26][27][28][29]. HIV-1 integration is influenced by a number of different factors including base composition [30], Alu repeats [31,32] and DNase I hypersensitive sites [33] and is directed by LEDGF/p75, a cellular binding partner of lentiviral integrases [34,35].…”
Section: Potential Adverse Effects Attribu-table To Lentiviral Vectorsmentioning
confidence: 99%